2007
DOI: 10.1249/mss.0b013e3180a74228
|View full text |Cite
|
Sign up to set email alerts
|

Immunoendocrine Response to Cycling following Ingestion of Caffeine and Carbohydrate

Abstract: Taken together, this suggests that coingestion of caffeine and CHO has greater influence on immunoendocrine responses than neutrophil functional responses to prolonged exercise.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
40
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(50 citation statements)
references
References 26 publications
8
40
2
Order By: Relevance
“…These results were consistent with Walker et al 12 who demonstrated that cortisol levels were not augmented when 6.0 mg⋅kg −1 caffeine was ingested before cycling exercise at 65% of V O2max for 120 min. Conversely, the results of the current study were not consistent with Bishop et al 23 who demonstrated that epinephrine and lymphocyte levels were augmented when caffeine was ingested at 6.0 mg⋅kg −1 before cycling exercise at 70% of V O2max for 90 min.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…These results were consistent with Walker et al 12 who demonstrated that cortisol levels were not augmented when 6.0 mg⋅kg −1 caffeine was ingested before cycling exercise at 65% of V O2max for 120 min. Conversely, the results of the current study were not consistent with Bishop et al 23 who demonstrated that epinephrine and lymphocyte levels were augmented when caffeine was ingested at 6.0 mg⋅kg −1 before cycling exercise at 70% of V O2max for 90 min.…”
Section: Discussionsupporting
confidence: 92%
“…11 The effects of caffeine ingestion before endurance exercise have been commonly studied. 3,12,13 However, less is known concerning the effects of caffeine ingestion before resistance exercise.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies report that carbohydrate prevents a decline in neutrophil elastase release (3) and oxidative burst activity (25), whereas other studies demonstrate no effect of carbohydrate (2,(22)(23)(24)26). These discrepant findings are likely due to variation in various factors including exercise protocols, the training status of subjects, timing of blood samples and assays of neutrophil function (27,28).…”
Section: Discussionmentioning
confidence: 99%
“…Of the handful of studies that have been published, all have administered 6 mg kg -1 body mass caffeine in one bolus dose following a 60-h abstinence period (Bishop et al 2005Fletcher and Bishop 2010a;Walker et al 2006Walker et al , 2007Walker et al , 2008. However, caffeine is typically consumed in separate doses throughout the day, following an overnight abstention (Fredholm et al 1999).…”
Section: Introductionmentioning
confidence: 99%